NADPH: ferredoxin oxidoreductase acts as a paraquat diaphorase and is a member of the soxRS regulon. - Liochev, S I (1994)
Soluble extracts of Escherichia coli contain four NADPH:paraquat diaphorases that were separable by anion-exchange HPLC over Mono Q. One of these was induced when the cells were exposed to paraquat. This was the case in a soxRS-competent strain but not in a soxRS-null strain, while a soxRS-constitutive strain overexpressed this diaphorase without the stimulus of exposure to paraquat. This NADPH:paraquat diaphorase could use cytochrome c or nitroblue tetrazolium as an electron acceptor, whereas O2 was a relatively poor acceptor. This diaphorase was identified as the NADPH:ferredoxin reductase. A role for reduced ferredoxin and flavodoxin in the adaptive soxRS response to oxidative stress and in the regulation of the redox status of soxR is discussed.